Pengembangan Alat Evaluasi Pembelajaran Matematika Berbasis Two Tier Multiple Choice Berlevel HOTS Menggunakan Ispring Suite 9 - Afifah, Wardhatus; Edy, Sarwo; Huda, Syaiful (Postulat : Jurnal Inovasi Pendidikan Matematika, 2022)
The purpose of this study was to develop an evaluation tool based on two tier multiple choice with HOTS level using ispring suite 9 which can be used online and can familiarize and hone students' higher order thinking skills. Because considering the current curriculum is the 2017 revised K13 which integrates with 4C and HOTS. The research and development model used is 4D. The research instruments used were interview sheets, validation sheets, test instruments, and questionnaires. Data analysis techniques used qualitative and quantitative. The results of the study can be seen from: Valid criteria based on the percentage of media experts by 97% and material experts by 89%, both categories are very feasible. The effective criteria based on the percentage of students' questionnaire responses were 76% in the interesting category. As well as the quality of the items seen from the validity there are 9 valid questions, the reliability is 8 reliable questions, the level of difficulty is obtained a percentage of 80% moderate, 10% difficult and 10% easy, the distinguishing power is obtained 6 good questions, 2 good enough, 1 very good question , and 1 question was bad, the effectiveness of the trick was 7 options selected by less than 2 students.